2007
DOI: 10.1007/s10549-007-9833-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiologic features of inflammatory breast cancer: a comparison between Egyptian and US patients

Abstract: Background-Inflammatory breast cancer (IBC) is a lethal form of breast cancer with unknown etiology. A higher frequency of IBC and a more aggressive IBC phenotype was reported in Egypt than in the U.S. This difference in disease frequency and presentation might be related to molecular epidemiologic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 31 publications
3
34
1
Order By: Relevance
“…Very little is known about IBC in Sub-Saharan Africa. Our studies and other studies mainly from Tunisia [14, 15], have depicted a higher proportion of IBC in North Africa compared to the U.S. [14]. Further studies are required to better define IBC in Sub-Saharan Africa with possible investigation into the association of infections with breast cancer incidence.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Very little is known about IBC in Sub-Saharan Africa. Our studies and other studies mainly from Tunisia [14, 15], have depicted a higher proportion of IBC in North Africa compared to the U.S. [14]. Further studies are required to better define IBC in Sub-Saharan Africa with possible investigation into the association of infections with breast cancer incidence.…”
Section: Discussionmentioning
confidence: 48%
“…Our studies and others have shown a higher proportion of IBC patients in populations in North Africa compared to the U.S. [1416] and distinct molecular features of the IBC cases in North Africa [17]. However, little is known about the rate or molecular features of IBC in other parts of Africa.…”
Section: Introductionmentioning
confidence: 47%
“…The Egyptian patients and their tumor characteristics are included in our previous publications [19,20]. Briefly, 41 IBC patients from the National Cancer Institute of Cairo University (NCI-Cairo), and 7 patients from the Gharbiah Cancer Registry in Tanta, were recruited during the period of September,2005 to December, 2006.…”
Section: Methodsmentioning
confidence: 99%
“…In this study the average age was 46.5 years and the majority of the patients (61.3%) were actually less than 50 years old. Elsewhere in Africa, some authors have even reported series with a lower average age, close to 40 years [15] [16].…”
Section: ) Epidemiological Characteristics -Frequencymentioning
confidence: 99%